2001
DOI: 10.1074/jbc.m106601200
|View full text |Cite
|
Sign up to set email alerts
|

Plant Mitochondrial Polyadenylated mRNAs Are Degraded by a 3′- to 5′-Exoribonuclease Activity, Which Proceeds Unimpeded by Stable Secondary Structures

Abstract: Recently, we and others have reported that mRNAs may be polyadenylated in plant mitochondria, and that polyadenylation accelerates the degradation rate of mRNAs. To further characterize the molecular mechanisms involved in plant mitochondrial mRNA degradation, we have analyzed the polyadenylation and degradation processes of potato atp9 mRNAs. The overall majority of polyadenylation sites of potato atp9 mRNAs is located at or in the vicinity of their mature 3-extremities. We show that a 3-to 5-exoribonuclease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…However, using oligo(dT)-based RT-PCR approaches, we and others (22)(23)(24)(25) have shown that mRNAs may be polyadenylated at low levels. The use of the cRT-PCR technique allows in theory the analysis of both the 3Ј-and 5Ј-ends of transcripts regardless of the polyadenylation status of the transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…However, using oligo(dT)-based RT-PCR approaches, we and others (22)(23)(24)(25) have shown that mRNAs may be polyadenylated at low levels. The use of the cRT-PCR technique allows in theory the analysis of both the 3Ј-and 5Ј-ends of transcripts regardless of the polyadenylation status of the transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in animals, plants, and in certain protist mitochondria, polyadenylation regulates mRNA stability (for review, see Gagliardi et al 2004). Apparently, mitochondrial polyadenylation is absent in S. cerevisiae (Gagliardi and Leaver 1999;Gagliardi et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, in these less complicated systems, polyadenylation of mitochondrial message might provide an organizing center for nuclease(s) to begin digesting the 3′ end. Recent work in potato mitochondria (Gagliardi et al, 2001) provides support for the idea that 3′ polyadenylation promotes 3′-5′ degradation. While differences in the mechanism of degradation may exist between plant and animal mitochondria on one hand, and chloroplasts and eubacteria on the other, the relationship between elevated polyadenylation and increased degradation appears to have been conserved between these groups (Gagliardi et al, 2001).…”
Section: Discussionmentioning
confidence: 88%
“…Recent work in potato mitochondria (Gagliardi et al, 2001) provides support for the idea that 3′ polyadenylation promotes 3′-5′ degradation. While differences in the mechanism of degradation may exist between plant and animal mitochondria on one hand, and chloroplasts and eubacteria on the other, the relationship between elevated polyadenylation and increased degradation appears to have been conserved between these groups (Gagliardi et al, 2001). Animal mitochondria typically contain very little non-coding DNA and have extremely compacted coding regions, while chloroplasts and plant mitochondria are generally much larger and contain genes not found in animal mtDNA, relatively more noncoding Stability and polyadenylation of mRNA during quiescence DNA, and intergenic spacers and UTRs that could serve as cisprocessing signals (Scheffler, 1999).…”
Section: Discussionmentioning
confidence: 88%